Influence of Mixture Composition and Compaction Pressure of Briquette Made from Ironwood (Eusideroxylon Zwageri) Charcoal and Gelam (Melaleuca Cajuputi ) on Combustion Characteristic - Syarief, Akhmad; Awaly, Nuryasin Qadimil; Yusuf, Muhammad; Iberahim, Jerry (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
In recent few years, many works have been dedicated to search for new source of renewable energy. In this study, new source of renewable energy is based in the briquette made from mixture of ironwood (Eusideroxylon zwageri) powder and gelam (Melaleuca leucadendron) wood powder. The mixture was carbonized at temperature of 500 oC Â± 10 oC for 120 minutes. The size of the particles used was 50 mesh while the ratio between wood powder adhesives, i.e. starch powder, used in the study was 1:1. The composition variations between ironwood charcoal and gelam were 100% ironwood charcoal powder and 0% gelam, 70%: 30%, 50%: 50%, 30%: 70%, 0% ironwood: 100% gelam. The compaction pressure during briquette production was varied at 100 kg/cm2, 125 kg/cm2 and 150 kg/cm2. Â The highest combustion temperature at 205 oC occurred in the specimen with composition of 30% ironwood powder and 70% gelam wood powder with compaction pressure of 100 kg/cm2. The longest burning duration 140 minutes (2 hours 20 minutes) occurred at composition of 50% ironwood powder and 50% gelam wood powder at compaction pressure of 150 kg/cm2. The fastest initial ignition time was 7 minutes and occurred for mixture with composition of 70% ironwood powder and 30% gelam wood powder at compaction pressure of 125 kg/cm2.